The Receptor for Advanced Glycation Endproducts Does Not Contribute to Pathology in a Mouse Mesenteric Ischemia/Reperfusion-Induced Injury Model - Wu, Mike C. L.; Gilmour, Timothy D.; Mantovani, Susanna; Woodruff, Trent M. (Frontiers in Immunology, 2015)
The receptor for advanced glycation endproducts (RAGE) can engage a diverse class of ligands and contribute to the immune and inflammatory response to infection and injury. It is known to be a pathogenic receptor in many inflammatory diseases, including ischemia/reperfusion (IR) injuries in several tissues, however, its role has not been investigated in IR injuries of the intestine to date. Mesenteric (or intestinal) IR leads to recruitment of inflammatory cells into intestinal interstitial spaces, which markedly disrupts intestinal mucosa. IR-induced mucosal injury is accompanied by the development of a local and systemic inflammatory response and remote organ injury, and results in high mortality in the clinic. We hypothesized that elimination of RAGE signaling using RAGE-/- mice would result in decreased local and remote organ injury and reduced inflammation in a mesenteric IR model, and thus be a target for therapeutic intervention. We found that RAGE ligands including HMGB-1 and C3a were elevated after mesenteric IR indicating the potential for enhanced RAGE activation in this model. However despite this, wild-type and RAGE-/- mice both displayed similar degrees of mesenteric injury, neutrophil infiltration, intestinal edema, cytokine generation, neutrophil mobilization and remote organ injury after mesenteric IR. We therefore conclude that despite its role in other organ IR injuries, and the robust production of RAGE ligands after intestinal ischemia, RAGE itself does not directly influence tissue injury and the inflammatory response in mesenteric IR.